Media Synchronicity Environmental Communication Perspective Rehabilitate Rivers from Domestic Waste - Heni Nuraeni Zaenudin; Sumardjo; Sarwititi Sarwoprasodjo; Amiruddin Saleh (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Abstract. Nowadays, the world is experiencing climate change and water pollution which can have bad impact on many aspects. Thus, the purpose of this study is to analyze the relationship between media synchronicity and task performance and communication performance in rehabilitating rivers from domestic waste in the Citarum Harum program. This study uses survey and the withdrawal technique uses multi-clustering, by choosing an area that is very close to the river which is the target of the Citarum Harum Program. The population is taken from two villages in Bandung Regency with heavily polluted river water quality status and uses multiple correlation coefficients and structural equation modeling partial least squares 3 as the data analysis technique. It shows a weak relationship between communication process variables and task performance and a negative relationship between the effects of moderation on communication performance. So, it is necessary to develop further models to improve these sub-variables.